Children Intrinsic Reading Motivation and Playful Applications: Investigating the Relationship - Aamri, F.; Greuter, S.; Walz, Steffen (2016)
Current research suggests that children who read for pleasure are intrinsically more motivated than children who rarely read for pleasure. Recent research also indicates that children who read from e-books are more intrinsically motivated to read than children who read from traditional print books. The current trend in e-books suggests that interactive and playful content assists children to stay motivated when reading and enhance their understanding of the content. However there is a lack of research on the effects of reading from interactive and playful e-books on intrinsic reading motivation. This paper discusses how we adapted existing reading motivation scales to derive a scale to measure Intrinsic Reading Motivation. We used this scale to compare the intrinsic reading motivation scores of 18 Omani fourth grade children after reading from a playful interactive storybook application, standard e-books, and traditionally printed books. The results showed that girls were slightly more influenced by the playful application than boys. However, children with the same reading skills obtained similar intrinsic reading motivation scores regardless of the reading format.